2015
DOI: 10.1155/2015/507196
|View full text |Cite
|
Sign up to set email alerts
|

Personal Strengths and Health Related Quality of Life in Dementia Caregivers from Latin America

Abstract: The research literature has begun to demonstrate associations between personal strengths and enhanced psychosocial functioning of dementia caregivers, but these relationships have not been examined in the context of dementia caregivers in Latin America. The present study examined whether personal strengths, including resilience, optimism, and sense of coherence, were associated with mental and physical health related quality of life (HRQOL) in 130 dementia caregivers in Mexico and Argentina. Structural equatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
31
1
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 67 publications
(72 reference statements)
3
31
1
5
Order By: Relevance
“…An alternative explanation is that the effects of the wisdom resources and social supports may be stronger on life satisfaction than on physical health because those resources are more likely to correlate with psychological health than physical health. This is consistent with previous studies showing that psychosocial resilience resources (e.g., optimism) are less likely to relate to physical well-being than to psychological well-being (Nygren et al, 2005; Trapp et al, 2015). They suggested that psychological resources might not directly relate to physical well-being of caregivers as strongly as they do to psychological well-being.…”
Section: Discussionsupporting
confidence: 93%
“…An alternative explanation is that the effects of the wisdom resources and social supports may be stronger on life satisfaction than on physical health because those resources are more likely to correlate with psychological health than physical health. This is consistent with previous studies showing that psychosocial resilience resources (e.g., optimism) are less likely to relate to physical well-being than to psychological well-being (Nygren et al, 2005; Trapp et al, 2015). They suggested that psychological resources might not directly relate to physical well-being of caregivers as strongly as they do to psychological well-being.…”
Section: Discussionsupporting
confidence: 93%
“…Our study showed a significant relationship between resilience and caregivers' QoL. Resilience is considered to act as a protective factor by increasing the QoL, coping and overall adaptation to difficulties related to caregivers 11 . The QoL involves the individuals' subjective perceptions about their role in life, based on their culture and system of values 28 .…”
mentioning
confidence: 50%
“…In contrast, the sense of coherence depends on the ability to realize that the situation is understandable or predictable and to perceive one' s ability to cope in a difficult situation and to find meaning in everyday events or problems faced 11 .…”
mentioning
confidence: 99%
“…A Spanish version of The Short Form Health Survey (SF‐36; Ware, Snow, Kosinski, & Gandek, ) was used to measure mental and physical HRQOL. The Spanish version of the SF‐36 has been effectively applied to neurorehabilitation caregiver studies within Latin America (Arango‐Lasprilla et al, ; Mickens, Perrin, Aguayo, Macias, & Arango‐Lasprilla, ; Trapp et al, ). The SF‐36 assesses social functioning, physical functioning, emotional role‐limitations, physical role‐limitations, mental health, general health, vitality, and pain.…”
Section: Methodsmentioning
confidence: 99%